PENGARUH PERILAKU KONSUMEN, BRAND IMAGE DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN ONLINE PADA SITUS BELANJA ONLINE (Studi Kasus pada Situs Belanja Online XYZ) - Bawono, Adhi; Isanawikrama, Isanawikrama; Arif, Kusumah; Kurniawan, Yohanes Jhony (Universitas Bunda Mulia, 2018)
ABSTRACT E-Commerce is electronic commerce related to the activity of buying, selling, marketing of goods or services by utilizing internet communication network as a form of future trading.. The purpose of this research is (1) To know the influence of consumer behavior toward online purchasing decision on E Commerce Site, (2) to know the influence of brand image to online purchasing decision on E Commerce Site, (3) to know the influence of promotion to online purchasing decision at E-Commerce Sites XYZ. The method used in this study is a quantitative research method and use if the data SPSS Version 24.00. Populations and samples (questionnaires) in this study were 97 valid questionnaires. Questionnaire materials include: Functional Image (image seen from product function), Affective Image (image seen from attitudes toward brand), and Reputation (image seen from reputation of brand) disseminated to E Commerce Site XYZ user in Jakarta. this is: Based on the results of research and discussion, it can be concluded as follows: (1) Partially, the dimensions of Consumer Behavior have a significant and positive effect on Purchase Decision at E-Commerce Sites XYZ received with a significance value of 0.618, (2) Partially, image has a significant and positive effect on Purchasing Decision at E Commerce Site XYZ received with a significance value of 0.323, (3) Partially, the promotion dimension has a significant and positive effect on Purchase Decision at E Commerce Sites received with a significance value of 0.765. Keywords: Consumer Behaviour, Brand Image, Promotion and Online Purchasing Decision.